2013
DOI: 10.1111/jcom.12006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Communication Infrastructure Theory for Informing Efforts to Reduce Health Disparities

Abstract: Communication infrastructure theory (CIT) offers an ecological approach to studying ways to reduce health disparities. The theory suggests that individuals' connections to a multi‐level storytelling system are enabled or constrained by the communication environment (a.k.a. communication action context). This article is a culmination of research to date that explores the potential of CIT to inform efforts directed at the reduction of health disparities. These studies have focused on geographic communities and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 51 publications
3
36
0
1
Order By: Relevance
“…In addition, research has demonstrated that integrated connections to health storytelling networks consisting of media, organizations, and interpersonal channels can lead to positive health outcomes (Wilkin, 2013). Thus, the main focus of this study was to determine if Spanish-language television provides information that connects viewers to a health storytelling network.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, research has demonstrated that integrated connections to health storytelling networks consisting of media, organizations, and interpersonal channels can lead to positive health outcomes (Wilkin, 2013). Thus, the main focus of this study was to determine if Spanish-language television provides information that connects viewers to a health storytelling network.…”
Section: Discussionmentioning
confidence: 98%
“…Recent research also demonstrates that individuals' connections to a dynamic neighborhood storytelling network are often related to health outcomes (Wilkin, 2013). For example, integrated connections to a neighborhood storytelling network are positively related to exercising (Wilkin, Katz, Ball-Rokeach, & Hether, 2015), performing emergency preparedness behaviors (Kim & Kang, 2010), seeking health information (Kim & Kang, 2006), and knowing more about preventing and detecting breast cancer and diabetes (Kim, Moran, Wilkin, & Ball-Rokeach, 2011).…”
Section: Communication Infrastructure Theory and Healthmentioning
confidence: 95%
“…Prior CIT research related to health had concentrated primarily on the neighborhood storytelling network, measured as the extent to which residents have integrated connections to an interpersonal network of neighbors, community organizations, and local=ethnic media (Wilkin, 2013). However, the communication infrastructure includes more potential health storytellers than those incorporated within the storytelling network (Wilkin & Ball-Rokeach, 2006, 2011.…”
Section: Contributions To Communication Infrastructure Theorymentioning
confidence: 97%
“…While much of the CIT research has concentrated on the STN, other ''storytellers'' can influence obesity-prevention behaviors (Wilkin, 2013). Researchers have begun engaging CIT to examine family communication as a unique storyteller within the larger storytelling system, which may also provide opportunities to engage with the STN.…”
mentioning
confidence: 99%
“…Research also suggests that CIT is helpful for identifying where and how researchers and health professionals might intervene to reach populations labeled "hard to reach" and reduce health disparities (Matsaganis, Golden, & Scott, 2014;Wilkin, 2013). In an intervention project that sought to lower the number of residents who relied on 911 and emergency departments for health care and to increase utilization of a local, federally funded health-care center, Wilkin, Stringer, O'Quin, Montgomery, and Hunt (2011) described strategies for engaging residents that were informed by an analysis of the local CAC's makeup.…”
Section: Communication Infrastructure Theorymentioning
confidence: 98%